The concept of conducting innovative competence of teachers in the space of educational activities - Maftyn, Larysa; Honcharuk, Vitalii; Pohoda, Olena; Popovych, Sergii; Fedorenko, Olena; Filipchuk, Nataliia (Laplage in Journal, 2021)
The article proposes the concept of the formation of the teacher's innovative competence in the educational space; it includes the initial ideas, goals, objectives, patterns, principles, stages, content and technologies for the implementation of this process; the concept is concretized at the level of strategy and implemented considering the developed model of the formation of the teacher's innovative competence in the educational space; the criteria and levels of the formation of the teacher's innovative competence make it possible to assess the teacher's readiness to introduce innovations (the development and implementation of fundamentally new images of content and teaching technologies).
Keywords: Innovative teaching; Higher education; Teaching technology